Chitosan-based in-situ forming polyelectrolyte complexes for ciprofloxacin sustained release tablets - Malik, Ajay; Verma, Navneet; Sharma, Vijay (Creative Pharma Assent, 2025)
Background: It is not straightforward to create sustained-release (single-unit) oral dosage forms for hydrophilic medicines, which are highly soluble (10 mg/mL) in gastric fluids and have a high dose. This study is an attempt to utilize biopolymer Chitosan-based Polyelectrolyte complex as a retardant to develop and evaluate the sustained release tablet formulations (oral) of Ciprofloxacin hydrochloride. Methodology: Sustained-release tablets were prepared using the traditional wet granulation method, employing a neutralized chitosan solution (1% w/w) at 4°C in 1% acetic acid as the binder. Formulated tablets were assessed for pharmacopoeial and non-pharmacopoeial parameters, as well as in vitro 12-hour drug release studies. The different mathematical models were utilized to examine the pharmacokinetic parameters and elucidate the mechanism of drug release. Results and discussion: The sustained release of the drug for 12 hrs was confirmed through the in vitro release studies. Both formulations, CFX 2 and CFX 3 exhibited 97% and 98% cumulative drug release, respectively, after 12 hr. The dissolution profiles of both formulations were shown to be unaffected by the change in anionic polymers from one to two, as confirmed by dissolution profile comparison studies, with values of similarity factor (f2) 84 and of difference factor (f1) 2. The XRD studies confirmed the in situ formation of a polyelectrolyte complex between chitosan and anionic polymer, as evidenced by the presence of additional peaks in the diffractograms. Conclusion: The polyelectrolyte complexes not only provide a sustained drug release but also prevent the initial burst release of the the drug.